(untitled) (Baština, 2022)
The paper discusses the interaction and inter-relationship between culture and socio-technological changes caused by the development of digital media, with an overview of changes that are happening in the field of culture and cultural participation in the last few decades. These changes occur in the domain of audiences, cultural creativity, cultural institutions and cultural markets. Paying special attention to the participatory turn in the field of culture, the paper provides an overview of the main trends and innovations in the field of cultural creativity and dissemination of cultural goods given to digital media, which are illustrated by various practical examples. The review and analysis of the transformation of the cultural sphere offered in this paper may be of importance to cultural theorists and practitioners, individuals involved in the process of cultural creation or management of cultural institutions, and cultural policy makers.